Strategi Perencanaan Dan Pengembangan SDM Dalam Meningkatkan Kinerja Karyawan Di Ramayana Padang - Rendy Zaputra; Firdaus Firdaus; Dewina Putri; Nadia Nadia; Ramdani Bayu Putra (CV. ITTC INDONESIA, 2025)
Human resources (HR) is an important asset in a company because the success of the company depends heavily on the quality and performance of employees. Therefore, planning and development of human resources becomeone aspect of the strategy that needs serious attention from the management Ramayana padang as one of the retail business units that is quite large in the city padang, is required to continuously improve the competitiveness and quality of service to customers. In the face of intense market competition and changes in consumer behavior, employees are required to be able to work effectively, efficiently, and professionally. To achieve this, a strategic HR planning and development strategy is needed to ensure that the company has a workforce that is competent, motivated, and ready to face business challenges as well as on target and sustainable. Good HR planning includes calculating workforce needs, mapping competencies, and systematic career management. Meanwhile, HR development can be done through training, coaching, mentoring, and other competency improvement programs. With the right strategy, companies are not only able to improve employee performance, but also create a productive and competitive work environment. Through this paper, we examine how HR planning and development strategies are implemented in the company Ramayana Padang, and the extent of its impact on improving employee performance. We hope that the results of our observations and interviews will contribute to more effective HR strategies in the future. The implementation of this system resulted in a more precise allocation of human resources according to operational needs. Ramayana Padang has succeeded in reducing overstaffing during low season and ensuring sufficient personnel during peak season, especially during major promotional periods such as Lebaran and year-end. Mapping competencies required to support the company's strategic direction and identifying gaps with available competencies. Ramayana Padang took the innovative step of implementing an artificial intelligence-based workforce optimization system. The system is designed for more accurate prediction of staffing needs with machine learning algorithms that take into account more than 25 business variables, dynamic scheduling that adjusts in real-time based on visitor traffic and sales volume, personalization of competency development based on analysis of individual performance patterns, automatic recommendations for internal mobility based on competency fit and organizational needs Strategies used by Ramayana Padang for HR development.